2006
DOI: 10.1029/2006wr004948
|View full text |Cite
|
Sign up to set email alerts
|

Straining of colloidal particles in saturated porous media

Abstract: [1] Straining may influence the mobility of colloid-sized particles within groundwater aquifers as well as within granular filters that are used in wastewater treatment. We conducted column transport experiments using latex microspheres as the colloids and quartz sand as the porous medium to investigate the response of colloid straining to changes in colloid diameter (d p ) and sand grain diameter (d g ). For these experiments the negatively charged microspheres were suspended in deionized water, and the quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(160 citation statements)
references
References 37 publications
9
149
2
Order By: Relevance
“…Our analysis suggested that the high attached phase concentration at the inlet was due to straining processes, which were considered to be dependent on the distance from the inlet. The average ratio of droplet diameter and the grain diameter in this study is in the range of 0.006-0.007, which is within the reported threshold (0.002-0.008) (Bradford et al, 2005;Xu et al, 2006) of straining for colloids with diameters of 0.5-5.1 μm. Finally, the simulated mass balance results matched very well with the experimental data (Table 4), which further confirms the validity of model.…”
Section: Vegetable Oil Droplet Transport and Retentionsupporting
confidence: 54%
“…Our analysis suggested that the high attached phase concentration at the inlet was due to straining processes, which were considered to be dependent on the distance from the inlet. The average ratio of droplet diameter and the grain diameter in this study is in the range of 0.006-0.007, which is within the reported threshold (0.002-0.008) (Bradford et al, 2005;Xu et al, 2006) of straining for colloids with diameters of 0.5-5.1 μm. Finally, the simulated mass balance results matched very well with the experimental data (Table 4), which further confirms the validity of model.…”
Section: Vegetable Oil Droplet Transport and Retentionsupporting
confidence: 54%
“…Under this condition, straining -that is the physical entrapment of the particles by constrictions in the porous medium -is usually considered to be insignificant. However, recently [Bradford et al, 2004;Xu et al, 2006] have suggested that this mode of deposition should occur at a ratio of as low as 5.10 À3 . Our results confirm that deposition at grain contacts plays a key role in the clogging process, and that microstructural information is needed to provide a detailed description of the formation of particle aggregates within pores.…”
Section: Resultsmentioning
confidence: 99%
“…Filtration models, summarized by [McDowell-Boyer et al, 1986;Elimelech et al, 1995;Tufenkji and Elimelech, 2004], normally assume fixed pore geometry and parameterize deposition rates in terms of the size ratio between mobile suspended particles and pore spaces. Recent investigations have shown that the internal variability of the porous medium plays an important role in the overall filtration process, and that enhanced deposition can be caused by straining at grain contacts [Johnson et al, 1996;Bradford et al, 2004;Li et al, 2006;Xu et al, 2006]. In addition, numerical simulations suggest that depositing particles form complex structures [Wiesner, 1999], and accumulation of deposited particles will eventually alter the pore geometry to a significant extent, leading to a reduction of permeability and producing clogging of the porous medium [Mays and Hunt, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The straining of colloids were more dominant for large, irregular shape, and multi-disperse colloids [84][85][86]. Straining of colloids in the unsaturated porous media become very complex due to the presence of gaseous phase.…”
Section: Attachment Of Colloid By Strainingmentioning
confidence: 99%